Phase-Amplitude Coupling Is Elevated in Deep Sleep and in the Onset Zone of Focal Epileptic Seizures - Amiri, Mina; Frauscher, Birgit; Gotman, Jean (Frontiers in Human Neuroscience, 2016)
The interactions between different EEG frequency bands have been widely investigated in normal and pathologic brain activity. Phase-amplitude coupling (PAC) is one of the important forms of this interaction where the amplitude of higher frequency oscillations is modulated by the phase of lower frequency activity. Here we studied the dynamic variations of PAC of high (gamma and ripple) and low (delta, theta, alpha and beta) frequency bands in patients with focal epilepsy in different sleep stages during the interictal period, in an attempt to see if coupling is different in more or less epileptogenic regions. Sharp activities were excluded to avoid their effect on the PAC. The results revealed that the coupling intensity was generally the highest in stage N3 of sleep and the lowest in rapid eye movement (REM) sleep. We also compared the coupling strength in different regions (seizure onset zone, exclusively irritative zone and normal zone). PAC between high and low frequency rhythms was found to be significantly stronger in the seizure onset zone compared to normal regions. Also, the coupling was generally more elevated in spiking channels outside the seizure onset zone than in normal regions. We also examined how the power in the delta band correlates to the PAC, and found a mild but statistically significant correlation between slower background activity in epileptic channels and the elevated coupling in these channels. The results suggest that an elevated PAC may reflect some fundamental abnormality, even after exclusion of sharp activities and even in the interictal period. PAC may therefore contribute to understanding the underlying dynamics of epileptogenic brain regions.